Household debt and macrodynamics: How do income distribution and insolvency regulations interact? - Nadja König (Hamburg University, Department Socioeconomics, 2016)
Using agent-based simulation methods we explore the interplay between income distribution, personal insolvency regulations and household borrowing focusing on the effects on macroeconomic dynamics. In order to capture the empirically observed distribution of income and wealth, we model them by means of a Generalised Pareto Distribution. In the presence of social comparison effects, the insolvency regime decides on lower income households' incentives to expose themselves to possibly unsustainable levels of debt. Our main findings can be summarised as follows: for both, creditor friendly and debtor friendly regimes, higher skewness in the distribution of income and wealth leads to an increase in the number of defaults and to lower levels of GDP. Comparing the two regimes, we observe a higher number of defaults and higher aggregate debt under pro-debtor laws given the same starting values for the distribution of income. While debt-financed consumption leads to higher levels of GDP under pro-debtor policies, over-borrowing low-income households put a downward pressure on economic growth. The opposite is true for pro-creditor policies, where we observe positive GDP growth rates, as they prevent households from taking up unsustainable levels of debt ex ante.
Keywords: D10; D31; E02; E21; 330; Optimal Insolvency Regulation; Income and Wealth distribution; Agent-based Model; Computational Simulation